PROMOTING LEARNER AUTONOMY IN A READING CLASS BY FACILITATING SELF-ACCESS LEARNING DURING THE COVID 19 PANDEMICS - Amelia Iswandari; ellen juita gultom (LINGUA : JURNAL ILMIAH, 2021)
Being an autonomous learner is one of the most important and universal purposes of foreign language education. Especially, when it comes to the situation when the students must practice independent study at home in this case due to the pandemics of Covid19 in Indonesia. This research investigates the application of a self-access language learning approach to foster learner autonomy in an emergency virtual reading class during the covid 19 pandemics of students in STBA LIA, Jakarta. It focuses on finding out how a self-access language learning approach fosters learner autonomy on virtual reading class during the pandemics; to what extent learners have the learning autonomy in the emergency virtual reading class. Qualitative analysis was done by describing data from two surveys and learners’ two assignments. The results show that a self-access language learning approach is beneficial to manage learning which promotes learner autonomy. Learners become more independent as they have to be responsible with their learning.